English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

C6H4(OH)2(aq) + H2O2(aq) C6H4O2(aq) + 2 H2O(l)

Calculate H for the above reaction from the following data.
C6H4(OH)2(aq) C6H4O2(aq) + H2(g) H = +177.4 kJ
H2(g) + O2(g) H2O2(aq) H = -191.2 kJ
H2(g) + 1/2 O2(g) H2O(g) H = -241.8 kJ
H2O(g) H2O(l) H = -43.8 kJ

Can i get a step by step demo please?

2007-11-04 01:16:25 · 1 answers · asked by summitgirl06 1 in Science & Mathematics Chemistry

1 answers

Want:
C6H4(OH)2(aq) + H2O2(aq) ==> C6H4O2(aq) + 2 H2O(l)

Given:
C6H4(OH)2(aq) ==> C6H4O2(aq) + H2(g), ∆H = +177.4 kJ..(1)
H2(g) + O2(g) ==> H2O2(aq), ∆H = -191.2 kJ...(2)
H2(g) + 1/2 O2(g) ==> H2O(g), ∆H = -241.8 kJ...(3)
H2O(g) ==> H2O(l), ∆H = -43.8 kJ...(4)
(1)-(2)+2(3)+(4):
C6H4(OH)2(aq) + H2O2(aq) ==> C6H4O2(aq) + 2 H2O(l),
∆H = 177.4+191.2-2*241.8-43.8 = -158.8 (kJ)

2007-11-04 05:37:55 · answer #1 · answered by Hahaha 7 · 0 0

fedest.com, questions and answers